Pengaruh Teknik Kompres Dingin terhadap Mobilisasi dan Intensitas Nyeri pada Pasien Pasca Operasi ACL: The Effect of Cold Compress Technique on Mobilization and Pain Intensity in Patients After ACL Reconstruction Surgery - Prihartini, Budi; Setiyowati, Yovita Dwi (Chakra Brahmanda Lentera Institute, 2026)
Pain and limited mobilization are major problems experienced by patients after Anterior Cruciate Ligament (ACL) reconstruction surgery. Uncontrolled postoperative pain may delay rehabilitation, reduce joint function recovery, and increase the risk of complications. The cold compress technique is a non-pharmacological nursing intervention that may help reduce pain intensity and improve mobilization in postoperative patients. This study used a descriptive case study design with a pre–post intervention approach. The participants were patients who underwent ACL reconstruction and were hospitalized in the inpatient ward of Hospital X. Pain intensity was measured using the Numeric Rating Scale (NRS), and mobilization was assessed by observing range of motion (ROM) and ambulation ability. Cold compress intervention was administered according to the standard operating procedure during the observation period. The findings demonstrated a reduction in pain intensity and improved mobilization following the application of the cold compress technique. The intervention reduced local inflammatory responses and enhanced patient comfort during the early rehabilitation phase. Cold compress therapy can be recommended as an evidence-based independent nursing intervention in the postoperative management of ACL reconstruction patients.